A facile green synthesis of LDH nanosheets using sugar molecules - Abdul Latip, Ahmad Faiz; Sivakumar, Mineesha; Mohd Suah, Faiz Bukhari; Hussin, Mohd Hazwan (Turkish Chemical Society, 2024)
The exfoliation of LDH materials is highly favorable for the formation of single-layer layered double hydroxides (LDH) nanosheets due to their unique chemical, thermal, optics, and biological properties. The green method for the exfoliation of layered double hydroxides (LDH) offers several advantages compared to conventional methods because it is considered safe, cost-effective, and eco-friendly. This report focuses on the exfoliation of layered double hydroxides (LDH) using sugar molecules as a green exfoliating agent without having to first pre-intercalate the layered material. The exfoliation of LDH is confirmed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), thermogravimetric (TGA), differential scanning calorimetry (DSC), and Brunauer-Emmett-Teller (BET) analyses. We also examined the crystalline phase of LDH in different stages of liquid exfoliation; suspension, semi-dry suspension, and dried solid samples using XRD. XRD data shows one broad peak for all the LDH exfoliated samples at 2θ = 23.9°,22.4°, and 22.3° respectively, which correspond to the characteristic (006) basal reflection of LDH single layers. These single peaks indicate the formation of LDH nanosheets. The higher intensity peak at the region 1000-1020 cm-1 for LDH exfoliated samples indicates the successful exfoliation of sugar molecules in the interlayer of LDH. In BET, the wide hysteresis loop for the exfoliated LDHs proved the successful exfoliation of sugar molecules into LDH layers. TEM images show ultrathin sheets of LDH and spherical-like particles. This work shows that LDH nanosheets can be obtained by using green biomolecules through simple synthetic methods.